Influence of COX-2-induced PGE2 on the initiation and progression of tail regeneration in Northern House Gecko, Hemidactylus flaviviridis - Sharma, P; Suresh, B (Folia biologica (Praha), 2008)
We investigated the role of prostaglandin E2 in reptilian regeneration. Prostaglandin E2 is known to play a vital role during wound healing and cell proliferation. A significant delay in the rate of growth of regenerate after autotomy was observed when the production of prostaglandin E2 was blocked by usage of specific cyclooxygenase inhibitors as compared to control animals and this delay continued to all the defined stages of regeneration. Therefore, prostaglandin E2 could be one of the essential requirements for a successful process of regeneration.
Keywords: pyrazoly; Cyclooxygenase Inhibitors; cyklooxygenasa 2; Sulfones; ještěři; Female; sulfonamidy; Cyclooxygenase 2; Tail; inhibitory cyklooxygenasy; zvířata; Dinoprostone; Pyridines; ženské pohlaví; Male; sulfony; pyridiny; regenerace; Lizards; Animals; dinoproston; mužské pohlaví; Pyrazoles; Sulfonamides; ocas; Regeneration